2017
DOI: 10.3390/molecules22040595
|View full text |Cite
|
Sign up to set email alerts
|

TCS2 Increases Olaquindox-Induced Apoptosis by Upregulation of ROS Production and Downregulation of Autophagy in HEK293 Cells

Abstract: Olaquindox, a feed additive, has drawn public attention due to its potential mutagenicity, genotoxicity, hepatoxicity and nephrotoxicity. The purpose of this study was to investigate the role of tuberous sclerosis complex (TSC2) pathways in olaquindox-induced autophagy in human embryonic kidney 293 (HEK293) cells. The results revealed that olaquindox treatment reduced the cell viability of HEK293 cells and downregulated the expression of TSC2 in a dose- and time-dependent manner. Meanwhile, olaquindox treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Our findings showed that knockout or knockdown of p53 effectively alleviated the activation of the JNK/p38 pathway (Figures 8(a) and 8(c) ), suggesting that p53 may act as the upstream of JNK/p38 pathways in OLA-induced toxicity. Our previous study demonstrated that JNK/p38 inhibitors (SP600125 and SB203580) significantly affected OLA-induced apoptosis [ 17 ], indicating that the JNK/P38 pathway participated in OLA-induced apoptosis. The JNK/p38 signaling pathway is activated or altered in a variety of cancers and regulates a variety of cellular processes including survival, proliferation, metabolism, angiogenesis, and metastasis [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings showed that knockout or knockdown of p53 effectively alleviated the activation of the JNK/p38 pathway (Figures 8(a) and 8(c) ), suggesting that p53 may act as the upstream of JNK/p38 pathways in OLA-induced toxicity. Our previous study demonstrated that JNK/p38 inhibitors (SP600125 and SB203580) significantly affected OLA-induced apoptosis [ 17 ], indicating that the JNK/P38 pathway participated in OLA-induced apoptosis. The JNK/p38 signaling pathway is activated or altered in a variety of cancers and regulates a variety of cellular processes including survival, proliferation, metabolism, angiogenesis, and metastasis [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, OLA played an important role in cell cycle arrest, which involved the activation of p53, GADD45a, p21, cyclin A, and Cdk2 protein [ 15 , 16 ]. Our previous study found that p21 knockdown regulated OLA-induced mitochondrial apoptosis and cell cycle arrest through the upregulation of AKT and downregulation of Nrf2/HO-1 pathways [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite its long-term argumentation toward the origin, phenotype, karyotype and tumorigenicity, the 293 cell line is one of the most commonly used cell models in cell biology studies due to its reliable growth and propensity for transfection. Therefore, the 293 cell line was used in the present study as a general cell model, without any particular purpose associated with the origin of the cell, for the study of cell autophagy that serves important physiological roles in a variety of cells (63)(64)(65).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have focused on the discovery of new compounds that act in these pathways, aiming to control exacerbated cell proliferation and autophagy. Among the alternative compounds that regulate autophagy by TSC2 are olaquindox, which induces autophagy and promotes apoptosis in HEK293 cells ( Li et al, 2017 ). Perhexiline, niclosamide, amiodarone (approved drugs) and rottlerin (pharmacological reagent) inhibit mTORC1 signaling and stimulate autophagy ( Balgi et al, 2009 ).…”
Section: Autophagy Therapies In Tsc- and Mtor-deficient Contextsmentioning
confidence: 99%
“… Role of lysine acetylation in TSC2, in the regulation of mTORC1, autophagy and cell proliferation; effects of treatments with nicotinamide and resveratrol on mTORC1 signaling and autophagy modulation are TSC2 -dependent Nicotinamide increased TSC2 acetylation, and lead to mTORC1 activation and cell proliferation. In contrast, resveratrol avoided TSC2 acetylation, inhibiting mTORC1 signaling and promoting autophagy GarcĂ­a-Aguilar et al ., 2016 A7r5 rat skeletal muscle biopsies from musculus vastus lateralis collected 72 h after the last training activity, and post-exercise biopsies collected 45 min after acute resistance exercise Cochaperone BAG3 stimulates translation through spatial regulation of mTORC1, inhibiting and recruiting the TSC complex to the cytoskeleton, where autophagy is initiated; mTORC1 inhibition in the remaining cytoplasm is relieved and translation efficiency increased BAG3 insufficiency results in a severe imbalance of protein synthesis and protein degradation, and in autophagic levels Kathage et al ., 2017 M HEK293 cells TSC2 acted as a negative regulator of autophagy after olaquindox treatment, and also played a pro-apoptotic function Olaquindox induced autophagy by reducing TSC2 expression in M HEK293 cells Li et al ., 2017 HeLa cells, primary human fibroblasts, human diploid fibroblasts, A MEF knock-out TsC2 and wild-type During the acquisition of senescence occurs the constitutive activation of mTORC1, which is resistant to both serum and amino acid starvation; persistent mTORC1 simultaneously prevents senescent cells from realizing their full autophagic potential, which would otherwise lead to cell death Constitutive mTOR activity in senescent cells was supported by high levels of autophagy, and increased autophagy contributes to mTORC1 deregulation and to the survival of senescent cells during starvation Carroll et al ., 2017 The generation of a TSC -cell model by isolating U NSPCs from the brain of six-week-old TsC1 mice. Migration deficit observed in Tsc1 -deficient U NSPCs depends on the state of TFEB activation; treatments that promote V TEFB nuclear translocation restore Tsc1 -deficient U NSPCs migation independently of mTORC1 …”
Section: Autophagy Therapies In Tsc- and Mtor-deficient Contextsmentioning
confidence: 99%